Aryl Hydrocarbon Receptor Activation in Astrocytes by Laquinimod Ameliorates Autoimmune Inflammation in the CNS. Issue 2 (6th March 2021) - Rothhammer, Veit; Kenison, Jessica E.; Li, Zahorong; Tjon, Emily; Takenaka, Maisa C.; Chao, Chun-Cheih; Alves de Lima, Kalil; Borucki, Davis M.; Kaye, Joel; Quintana, Francisco J.
Abstract : Objective: MS is an autoimmune demyelinating disease of the CNS, which causes neurologic deficits in young adults and leads to progressive disability. The aryl hydrocarbon receptor (AHR), a ligand-activated transcription factor, can drive anti-inflammatory functions in peripheral immune cells and also in CNS-resident cells. Laquinimod is a drug developed for the treatment of MS known to activate AHR, but the cellular targets of laquinimod are still not completely known. In this work, we analyzed the contribution of AHR activation in astrocytes to its beneficial effects in the experimental autoimmune encephalomyelitis (EAE) preclinical model of MS. Methods: We used conditional knockout mice, in combination with genome-wide analysis of gene expression by RNA-seq and in vitro culture systems to investigate the effects of laquinimod on astrocytes. Results: We found that AHR activation in astrocytes by laquinimod ameliorates EAE, a preclinical model of MS. Genome-wide RNA-seq transcriptional analyses detected anti-inflammatory effects of laquinimod in glial cells during EAE. Moreover, we established that the Delaq metabolite of laquinimod dampens proinflammatory mediator production while activating tissue-protective mechanisms in glia. Conclusions: Taken together, these findings suggest that AHR activation by clinically relevant AHR agonists may represent a novel therapeutic approach for the treatment of MS.